2021
DOI: 10.31435/rsglobal_ws/30082021/7657
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Modeling of Super-, Sub-Eye Patch and Chin Openings in Fruits and Newborn

Abstract: Using modern anatomical methods, 57 preparations of human fetuses 4-10 months and 7 newborns were studied in order to create models of distances of supra-, suborbital and chin openings between themselves and to standard landmarks in fetuses and newborns taking into account their morphometric parameters. The model of the distance from the supraorbital foramen to bregma (Y1): Y1 = β0 + 0.092 x parietal-heel length of the fetus, where β0 :: 2,783, if the age period = 4 months; 3,106 = 5 months; -0.662 = 6 months;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As a result of the study, it was found that among all the studied ethnic groups, SF, IF, MF were at a distance of 25.32 mm, 29.57 mm, and 25.55 mm from the midline, respectively [8]. V. O. Kostiuk and O. M. Slobodian using modern anatomical methods studied the distances between SF, IF, MF and to standard landmarks in fetuses and newborns, due to which they established the average values of the above-mentioned parameters in different age periods [11]. There is a large number of experiments related to the determination of the position of the MF relative to various structures, namely differences in the position of this foramen among different population groups, regardless of sex, age, and extreme types of the head [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the study, it was found that among all the studied ethnic groups, SF, IF, MF were at a distance of 25.32 mm, 29.57 mm, and 25.55 mm from the midline, respectively [8]. V. O. Kostiuk and O. M. Slobodian using modern anatomical methods studied the distances between SF, IF, MF and to standard landmarks in fetuses and newborns, due to which they established the average values of the above-mentioned parameters in different age periods [11]. There is a large number of experiments related to the determination of the position of the MF relative to various structures, namely differences in the position of this foramen among different population groups, regardless of sex, age, and extreme types of the head [13].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular-nerve bundles pass through SF, IF, and MF, and therefore, when performing complex surgical interventions, as well as during local anesthesia, it is extremely important to know the exact position of these foramens, and accordingly, the exit of nerve branches and vessels [1,9,10,15,22]. Further development of plastic and maxillofacial surgery is impossible without an in-depth and systematic study of the range of individual anatomical variability of the facial skull as a whole, features of its shape, size, position, and relationships of its structures [11,19,20,21]. Taking into account the types of skull structure, the studied craniometric parameters have pronounced individual differences, which confirms the existing range of variability of the profile anatomy of the facial skull [21].…”
Section: Introductionmentioning
confidence: 99%
“…Безпосередньо питанню дослідження збігу розподілів експериментальних даних присвячено значну кількість робіт, як фундаментальних посібників з теорії ймовірності та теорії експерименту, так і публікації з вирішення окремих приватних задач [9], [10], [11], [12]. Проте, слід відмітити, що до сьогоднішнього дня у відомій літературі немає єдиного підходу до термінів і визначень з цього питання.…”
unclassified